STUDENTS' READING COMPREHENSION AND THEIR TRANSLATING ABILITY - Endang Darsih, - (2011)
Translation is understood as a transfer process from a foreign language or a second language to the mother tongue or vice versa. There are some essential characteristics that any good translator should have. One of them is mastering reading comprehension. In other words, the quality of students' translation depends on their reading comprehension. Students who are good in comprehending the texts will be able to translate well too. With regard to this assumption, this study aims at investigating the correlation between students' reading comprehension and their translating ability. The study applied a descriptive method with a correlational design. The participants, 24 third year students of accounting department of SMKN 2 Kuningan, were selected purposively. A descriptive method was applied and Pearson Product Moment Correlation Coefficient was used to examine the correlation between the two variables; students' reading comprehension and their translating ability. There were two kinds of data resources: scores from their TOEIC reading comprehension section and scores from students' translation test. The findings revealed that r = 0.752 and it was considered to be positive and high. Since robs was greater than rtable, the null hypothesis (Ho) was then rejected. It means that there was a significant correlation between level of reading comprehension and translating ability. It can be proven from the evidence that the students who got a high level in reading comprehension tend to have good scores in translation. The higher the level of reading comprehension the participants have, the better the translation quality is.